1990
DOI: 10.1111/j.1365-2842.1990.tb01392.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between three ethnic groups to derive some standards for maxillary arch dimensions

Abstract: A sample of 91 adult Philippinos, 45 males and 46 females, were selected for maxillary arch measurements. The intercanine width (C-C), intermolar width (M-M), molar incisor (M-I) and molar canine (M-C) length were measured. The measurements were compared to previous studies of maxillary arch dimensions for adult male and female Egyptians and Saudi Arabians. The results showed wider (M-M) measurements for the Egyptians than for the Philippinos, who also showed wider (C-C) arch dimensions than the Saudi Arabians. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 4 publications
3
19
0
Order By: Relevance
“…Despite efforts in the Arab world during the last decades to make health systems more equitable[1415161718] access to dental healthcare is still far from adequate, especially in poor communities. In Yemeni population, there is no previous study carried out on the mandibular arch dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts in the Arab world during the last decades to make health systems more equitable[1415161718] access to dental healthcare is still far from adequate, especially in poor communities. In Yemeni population, there is no previous study carried out on the mandibular arch dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that there is a range of variation, either in structure, shape, size configuration or other distinct contrasting characteristics (Hardlicka, 1907;Pittard, 1926). A number of anthropologists have related maxillary arch development to different dietary, environmental and physical factors for various populations (Sawiris, 1977;Mack, 1981;Gridly & Daas, 1985;Sarhan & Diwan, 1987;Younes, Al Shammery & El Angbawi, 1988;Diwan & Elahi, 1990;Merz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In another study significant differences between the arch width measurements were found to exist between several classes of subjects based on race and sex [11]. The results of one research showed wider PAW for the Egyptians than for the Filipinos, who also showed wider AAW than the Saudi Arabians [12].…”
Section: Discussionmentioning
confidence: 91%